(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research revolves around the theory of reasons and causes between Mu’tazila and Ash’ari. I have chosen two teams from the speakers: Mu’tazila and Ash’ari as examples of the applications of this theory, because they are located on opposite sides. From the opinion of the Mu’tazilites, they make the connection between the reasons and the causes, obligatory, as they do not separate from each other. On the contrary Ashari state that the connection is normal, and the reasons work when the cause is not with it, and a difference between working with it and working with it. Each statement ineludes religious traces. Some of them are dealing with the creation of peoples actions.